Personalized atrial fibrillation ablation by tailoring ablation index to the left atrial wall thickness. the ablate by-law single center study. (24th May 2021) - Teres, C; Penela, D; Soto-Iglesias, D; Jauregui, B; Ordonez, A; Chauca, A; Carreno-Lineros, JM; Scherer, C; Huguet, M; Ramirez-Paesano, C; Oller, G; Panaro, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Dr Teres is funded by the research fellowship grant from the Swiss Heart Rhythm Foundation, Dr Carreno was funded was funded by a Scholarship from Sociedad Española de Cardiología (SEC). Introduction: Left atrial wall thickness (LAWT) is a determinant of transmural lesion formation during atrial fibrillation (AF) ablation. The utility of ablation index (AI) to dose radiofrequency (RF) delivery for the reduction of AF recurrences has already been proven with a target AI ≥ 400 at the posterior wall and ≥550 at the anterior wall. Objective: To determine if adapting AI to atrial wall thickness (AWT) is feasible, effective and safe during AF ablation. Methods: Consecutive patients referred for a first PAF ablation. LAWT 3D-maps were obtained from multidetector computed tomography (MDCT) and integrated into the CARTO navigation system. LAWT maps were semi-automatically computed from the MDCT as the local distance between the LA endo and epicardium and categorized into 1mm-layers and AI was titrated to the LAWT, as follows: Thickness < 1 mm (red): 300; 1-2 mm (yellow): 350; 2-3 mm (green): 400; 3-4 mm (blue): 450; > 4 mm (purple): 450 (Figure). The ablation line was designed in a personalized fashion to avoid thicker regions. All ablation procedures were performed under general anesthesia with a high frequency low-volume ventilation. Primary endpoints were acute efficacy and safety, and freedom from AF recurrences. Follow-up (FU) was scheduled at 1, 3, 6, and every 6 months thereafter. Results: 90 patients [60 (67 %) male, age 58 ± 13 years] were included. Mean LAWT was 1.25 ± 0.62 mm. Mean AI was 366 ± 26 on the right pulmonary veins (RPVs) with a first-pass isolation in 84 (93%) patients and 380 ± 42 on the left pulmonary veins (LPVs) with first-pass in 87 (97%). Procedure time was 59 min [49-66]; RF time 14 min [12, 5-16]; fluoroscopy time 0.7 min [0.5-1.4]. No major complication occurred. Eighty-six out of 90 (95.5%) patients were free of recurrence after a mean FU of 11 ± 4 months. Conclusions: Personalized AF ablation, adapting the AI to LAWT allowed decreasing RF delivery, fluoroscopy and procedure time while obtaining a high rate of first-pass isolation. Lesion durability as estimated by freedom from AF recurrences was as high as in more demanding ablation protocols.